Assessing knowledge, awareness, and perception of genetic testing for hereditary disorders in companion animals among pet owners in Klang Valley - Salisi, Mohd Shahrom; Muhammad Ibrahim, Panhwar; Radzi, Rozanaliza; Md. Ajat, Mohd Mokrish; Abdul Kadir, Arifah; A., Amalia (Malaysian Veterinary Medical Association, 2024)
To identify hereditary disorders in animals, it is necessary for them to go through genetic testing. When there is low awareness of the importance of genetic testing among pet owners, this will cause an increase in the incidence of hereditary disorders in their pets. The objective of this study was to assess the knowledge, awareness and perception of genetic testing in companion animals among local pet owners in Klang Valley, Malaysia and the potential variables that influence the pet owners ‘understanding of animal genetic testing. To achieve our objectives, an online survey was conducted targeting residents of different districts of Klang Valley with a total of 120 respondents gathered within 2 weeks period. Data collected was analysed for a descriptive statistic using IBM SPSS Statistics version 22.0. This questionnaire assessed the public’s knowledge, awareness, and perception of genetic testing. The self-administered questionnaire comprised of four sections focusing on the details of the respondents, including demographic characteristics, knowledge of genetic testing, awareness and perception of genetic testing. The results revealed that pet owners have satisfied knowledge and were highly aware of genetic testing in companion animals. The perception of genetic testing of the pet owners in Klang Valley, Malaysia was also generally positive. Based on the result, the variability of demographic background, such as educational background, influences the knowledge (p<0.01) and perception (p≤0.05) of genetic testing among pet owners in Klang Valley. Meanwhile, education background does not influence the awareness (p>0.05) of genetic testing among pet owners of Klang Valley, Malaysia.